Задача о дискретном построении образов - Донец, Г.А.; Альшаламе Самер (Теорія оптимальних рішень, 2004)
In this paper the problem of sample-aided discrete color imagary construction within rectangular field of vision in studied. It is shown that this problem can be reduced to solution of the modulo k residual system of linear algebraic eqations. Here solution is offered for the case of k = 2 and linear samples.